Pengetahuan dan Sikap Siswa SDN Ranah Singkuang dan SDN Pekanbaru dalam Memilih Pangan Jajanan - Sri Mulyani; Fitria Fitria (Jurnal Kesehatan Komunitas, 2023)
Background: Snack Food have an important role in fulfilling the energy and nutritional intake of school-age children, namely snack food that is safe, quality, and nutritious which will greatly determine the competitiveness of the golden generation of Indonesia. Objective: to analyze the description of the knowledge and attitudes of students at SDN Ranah Singkuang Kampar and SDN Pekanbaru in choosing snack food. Methods: This type of research is a descriptive study with a cross-sectional design. The study was conducted from January – September 2021. The samples in this study were students of SDN Ranah Singkuang Kampar and SDN Pekanbaru, grades 4 and 5, which were taken using a total sampling technique, totaling 240 people. The data was collected using a questionnaire and the data were analyzed univariately. Results: the study showed the level of knowledge of students about the selection of snacks and knowledge of hygiene and packaging of snacks in the "not good" category with a higher percentage of students at SDN Ranah Singkuang, which was 70%. Negative attitudes also tend to be shown by students of SDN Ranah Singkuang and students of SDN Pekanbaru towards hygiene and food packaging for snacks that are quite in accordance with the level of knowledge of students who are still quite good. Meanwhile, the habit of having breakfast and bringing lunch was better for students at SDN Ranah Singkuang than at SDN Pekanbaru. Conclusion: the knowledge and attitudes of students at SDN Ranah Singkuang are lower than those at SDN Pekanbaru.